Profil Ecoliteracy Peserta Didik Kelas VI di Sekolah Dasar - Malihanita, Safira; Saputri, Dwi Yuniasih (Didaktika Dwija Indria, 2026)
This study aims to describe the ecoliteracy profile of elementary school students. Ecoliteracy or ecological literacy is an important 21st-century competency that includes students' understanding of ecosystem concepts, attitudes toward the environment, and behavior in preserving nature. This study used a qualitative descriptive method with sixth-grade elementary school students as subjects. Data collection was conducted through interviews, observations, and documentation. The results showed that most students have a basic understanding of ecological concepts, demonstrate positive attitudes toward the environment, and have implemented several environmentally friendly actions at school and at home. However, there are still challenges in consistently integrating ecological activities into daily life. This study provides important insights for the development of environmentally-based curriculum and learning strategies in elementary schools. The implementation of the Problem Based Learning model assisted by flipbooks has proven effective in improving students' problem-solving abilities and environmental awareness, thus having implications for strengthening ecoliteracy from elementary school age.